Pengaruh Kualitas Layanan, Akses, Harga, dan Kompetensi Karyawan Terhadap Kepuasan Pelanggan PT Kereta Api Indonesia - Nila Badriyah; Arif Kuswanto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Indonesia's vast territory makes transportation one of the most important needs for Indonesian people. One of them is land transportation, of various kinds of land transportation, trains are one of the favorite transportation of the Indonesian people. By using the train, people can move from one area to another in a relatively short time and safely. PT Kereta Api Indonesia is a company that offers rail transportation services. One of the stations owned by PT Kereta Api Indonesia is Malang Kota Baru Station which is located in Malang City, East Java province, where this city is known as one of the tourist destinations of the Indonesian people. Therefore the management of the Malang Kota Baru Railway Station needs to provide satisfaction for customers who travel through this station. In the research being carried out, researchers will examine the effect of the variable dimensions of service quality, access, price, and employee competence on customer satisfaction at Malang City Baru Station. The type of research used is quantitative research using multiple linear regression analysis. The data was distributed using a questionnaire, and was addressed to 400 respondents who were passengers at Malang Kota Baru Station. The results showed that service quality and access variables had a significant influence on customer satisfaction. Meanwhile, other variables, namely price and employee competence, have no significant effect on customer satisfaction at Malang Kota Baru station.